Effective pressure and cell area distribution in a confined monolayer. (23rd August 2018) - Khain, Evgeniy; Tsimring, Lev S
Abstract: Contact inhibition limits cell growth and division after they form a monolayer and make lasting contact with each other. It has been shown, however, that the cell proliferation does not stop instantaneously upon forming contacts. The newborn daughter cells continue to grow after division, however to a smaller equilibrium size; thus the average cell size dramatically decreases with time. It has also been found that the dispersion in cell sizes decreases as well. In this paper we argue that these observations can be reproduced and explained by introducing an effective pressure that affects cell growth. We present a mathematical model that predicts the temporal evolution of cell size distribution in a closed system; the theoretical predictions are in a good agreement with recent experimental observations.